2022
DOI: 10.1111/jac.12583
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of photosynthesis under salinity and the role of mineral nutrients in Jatropha curcas L.

Abstract: Jatropha curcas is a common species in Brazil, potentially being an option to produce oil for bioenergetic purposes. Around the world, J. curcas has been cultivated in areas of low fertility, in the presence of salts, and with the use of brackish groundwater.Salt stress can hinder the absorption of nutrients and allow entry of ions in toxic concentrations, affecting the development and productivity of plants. This study aimed to evaluate the effect of salinity on the gaseous exchange and the dynamics of some m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
1
6
0
1
Order By: Relevance
“…Iron has a vital role as a component of the enzymes involved in the electron transport process [ 87 , 88 ]. In our experiment, the Fe levels were significantly increased in the aboveground tissues after 8 days of exposure of S. sclarea plants to Zn ( Table 1 ), with a concomitant increase in the electron transport rate (ETR) ( Figure 4 b).…”
Section: Discussionmentioning
confidence: 99%
“…Iron has a vital role as a component of the enzymes involved in the electron transport process [ 87 , 88 ]. In our experiment, the Fe levels were significantly increased in the aboveground tissues after 8 days of exposure of S. sclarea plants to Zn ( Table 1 ), with a concomitant increase in the electron transport rate (ETR) ( Figure 4 b).…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde content could reflect the final level of cell membrane disruption, the generation of MDA will be lower, indicating a lower level of cell membrane disruption (Shamsi et al, 2020;Bezerra-Neto et al, 2022). Lower values of MDA caused by a combination of enzymatic defense and osmotic adjustment in P. euphratica remained stable to avoid membrane damage in salt stress.…”
Section: Leaf Intracellular Traits Under Salinity Stressmentioning
confidence: 99%
“…By analyzing gas exchange in cowpea culture, Shoukat et al [57] reported that the salinity of irrigation water reduced gas exchange, resulting in a decrease in the following parameters: stomatal conductance; photosynthesis; growth; and production.…”
Section: Gas Exchangementioning
confidence: 99%